Dual curing UV tackifying adhesives and articles thereof

By using dual-curing UV adhesive-enhancing adhesive, the dual-curing process of thermal curing and UV light curing is solved, and the problems of difficult separation of traditional adhesives after pasting and poor heavy-working performance are achieved, efficient pasting and peeling are achieved, and the adhesive performance is improved. and fit yield.

CN119432262APending Publication Date: 2025-02-14CROWN TAICANG ADHESIVE PROD CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411567685.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Traditional adhesive tape is difficult to separate after being pasted, has poor heavy industry performance, and the tape after UV adhesive reduction cannot be used again, resulting in waste of materials.

Method used

Dual curing UV adhesive enhancer is used, which has a lower bonding strength in the early stage of adhesion by thermal curing, which facilitates positioning and peeling, and significantly increases the bonding strength after UV light curing.

Benefits of technology

It can be peeled off and re-pasted after being pasted and positioned, which improves the bonding yield and bonding performance and reduces material waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005119683600000021
    Figure BDA0005119683600000021
  • Figure BDA0005119683600000031
    Figure BDA0005119683600000031
  • Figure BDA0005119683600000151
    Figure BDA0005119683600000151
Patent Text Reader

Abstract

The invention relates to the technical field of adhesives, in particular to a dual-curing UV tackifying adhesive and a product thereof. The dual-curing UV tackifying adhesive is prepared from the following components in parts by weight: 73 to 92 parts of acrylate copolymer, 6 to 25 parts of UV polyester resin, 0.4 to 1.7 parts of thermal curing agent and 0.3 to 1 part of photoinitiator. According to the dual-curing UV tackifying adhesive disclosed by the invention, the components are compounded, so that the adhesive can be endowed with relatively low and appropriate bonding strength in a thermocuring stage, the bonding and positioning requirements are met, and the dual-curing UV tackifying adhesive can be stripped from an adhered object and has excellent reworkability; and after positioning, the bonding force between the adhesive and the pasted object is increased through UV illumination, so that the pasting effect of the adhesive on the pasted object is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, in particular to a dual-curing UV tackifying adhesive and a product thereof. Background Art

[0002] Traditional adhesive tapes are difficult to separate from the adhered object and have poor rework performance. Ultraviolet (UV) adhesive tapes currently on the market can generate free radicals or anions after UV light exposure to increase the density of the colloid cross-linking surface, thereby reducing the adhesive performance of the tape. However, during the use of the tape, if the pasting positioning is inaccurate and re-adhesion is required, the initial viscosity is too high, which will increase the complexity of the rework operation, and since the UV adhesive tape cannot be reused, it will lead to material waste.

[0003] Currently, UV monomers are introduced to reduce the adhesive properties of pre-UV colloids. However, the peeling force of the colloid before UV is still high, which makes it impossible to quickly peel and reposition it. In addition, the introduction of UV monomers has the problem of volatility, which will have adverse effects on the human body and the environment.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The invention provides a dual-curing UV tackifying adhesive and a product obtained from the adhesive. Before UV irradiation, the adhesive cured by heat has initial bonding performance that meets the requirements of pasting positioning; after positioning, further curing by UV can significantly improve the bonding strength and ensure the pasting effect.

[0006] In order to achieve the above-mentioned object of the present invention, the first aspect of the present invention provides a dual-curing UV tackifying adhesive, comprising the following components in parts by weight:

[0007]

[0008] The second aspect of the present invention provides an adhesive product made from the dual-curing UV tackifying adhesive provided by the first aspect of the present invention, the product comprising a substrate layer and an adhesive layer arranged on at least one side of the substrate layer; the adhesive layer is mainly made from the dual-curing UV tackifying adhesive described in the first aspect of the present invention.

[0009] Compared with the prior art, the present invention has the following beneficial effects:

[0010] (1) The dual-curing UV tackifying adhesive of the present invention has a low bonding strength to meet the pasting positioning requirements at the initial stage of pasting with the adhered object by compounding the various components through thermal curing, and can be re-adhered after peeling, has excellent reworkability, and can improve the pasting yield rate; after positioning, further UV light curing can increase the bonding strength between the adhesive and the adhered object, thereby ensuring the pasting effect of the adhesive on the adhered object;

[0011] (2) The preparation method of the dual-curing UV tackifying adhesive of the present invention is simple to operate; the prepared adhesive product has excellent reworkability before UV irradiation and excellent bonding performance after UV irradiation. DETAILED DESCRIPTION

[0012] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0013] The first aspect of the present invention provides a dual-curing UV tackifying adhesive, comprising the following components in parts by weight:

[0014]

[0015] The UV polyester resin refers to a polyester resin that can be cured under UV light.

[0016] The dual-curing UV tackifying adhesive of the present invention utilizes an acrylate copolymer and a thermal curing agent to carry out a thermal curing crosslinking reaction, thereby increasing the crosslinking degree of the adhesive and the modulus, so that the adhesive has a relatively low bonding strength that meets the positioning requirements before UV irradiation, has excellent reworkability, and improves the bonding yield. During the thermal curing process, the UV polyester resin mainly plays a plasticizing role in the adhesive system, which helps to appropriately reduce the peeling force. After positioning, UV light is further used for UV curing, and the UV polyester resin and the acrylate copolymer undergo a crosslinking reaction, which increases the surface energy of the adhesive surface of the adhesive system, increases the polarity, and gives the adhesive excellent bonding performance.

[0017] The inventors of the present invention have found that the UV polyester resin in the present invention plays different roles in the adhesive system before and after UV irradiation. At the same time, the amount of UV polyester resin used has a great influence on the performance of the adhesive. When the content of UV polyester resin is insufficient, the plasticizing effect on the adhesive system before UV irradiation is not obvious, and the viscosity-increasing effect after UV irradiation is not good; when the content of UV polyester resin is too high, on the one hand, it is easy to cause insufficient initial adhesion before UV irradiation, and on the other hand, the adhesion to the adhered object is too strong after UV irradiation, which will cause the tape to debond during subsequent peeling. The present invention can effectively balance the pasting positioning, reworkability, bonding strength and peelability by regulating the content of UV polyester resin in the adhesive system within a certain range.

[0018] For example, in different embodiments, in the dual-curing UV tackifying adhesive, the amounts of each component in parts by weight may be as follows:

[0019] The amount of the acrylate copolymer can be 73 parts, 75 parts, 78 parts, 80 parts, 82 parts, 85 parts, 88 parts, 90 parts, 92 parts or any value between any two end values; the amount of the acrylate copolymer in the adhesive is controlled within the above range, and the acrylate copolymer and the heat curing agent are cured and cross-linked in the heat curing stage to give the adhesive system a suitable bonding strength to meet the requirements of pasting positioning and have reworkability;

[0020] The amount of UV polyester resin can be 6 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts or any value between any two ends thereof;

[0021] The amount of the thermal curing agent can be 0.4 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.7 parts or any value between any two ends thereof;

[0022] The amount of the photoinitiator can be 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.8 parts, 1 part or any value between any two ends thereof.

[0023] In a specific embodiment of the present invention, the acid value of the UV polyester resin is ≤220 mgKOH / g, and can be 1 mgKOH / g, 5 mgKOH / g, 10 mgKOH / g, 25 mgKOH / g, 50 mgKOH / g, 80 mgKOH / g, 100 mgKOH / g, 120 mgKOH / g, 150 mgKOH / g, 180 mgKOH / g, 220 mgKOH / g or any value not exceeding the end value.

[0024] The term "acid value" refers to the number of milligrams of potassium hydroxide (KOH) required to neutralize 1 gram of a chemical. The higher the acid value, the more free carboxylic acid groups there are.

[0025] The term "functionality" refers to the number of functional groups in a molecule that can participate in a condensation reaction.

[0026] In a specific embodiment of the present invention, the functionality of the UV polyester resin is 3-4, specifically 3 or 4.

[0027] The functionality of UV polyester resin within the above range is more conducive to rapid polymerization under UV light conditions, improving the degree of crosslinking and achieving a tackifying effect. If the functionality of UV polyester resin is too small, it is not conducive to building a suitable crosslinking network structure, and the tackifying effect is not obvious; if the functionality of UV polyester resin is too large, excessive crosslinking may lead to excessively high modulus of UV polyester resin after polymerization, reducing the bonding strength to the object.

[0028] In a specific embodiment of the present invention, the UV polyester resin can be a commercially available product, such as ST6207 and ST6277 produced by Shanghai Santong Material Technology Co., Ltd., L-6125, L-6120, L-6129 produced by Guangdong Lanke Road New Materials Co., Ltd., etc.

[0029] In a specific embodiment of the present invention, the storage modulus of the dual-curing UV tackifying adhesive at 25°C after UV curing is 68 to 103 kPa, specifically 68 kPa, 73 kPa, 78 kPa, 82 kPa, 87 kPa, 93 kPa, 98 kPa, 103 kPa or any value between any two end values. The inventors of the present invention have found that when the adhesive of the present invention has a storage modulus within the above-defined range before UV curing, it is more helpful to regulate the adhesive system after thermal curing and before UV irradiation to have a suitable bonding strength, so as to achieve the effect of pasting positioning and being able to peel off from the adhered object.

[0030] In a specific embodiment of the present invention, the molecular weight of the acrylic ester copolymer is 100,000 to 1,300,000 g / mol, specifically 100,000 g / mol, 200,000 g / mol, 400,000 g / mol, 500,000 g / mol, 620,000 g / mol, 680,000 g / mol, 720,000 g / mol, 1,300,000 g / mol or any value between the two end values. When the acrylic ester copolymer within the above molecular weight range is used, if the molecular weight is too low, the copolymer will not be cohesive enough and it will be difficult to achieve effective bonding, and if the molecular weight is too high, the adhesive surface modulus will be too high and the bonding performance will be poor.

[0031] In a specific embodiment of the present invention, the solid content of the acrylic ester copolymer is 20% to 60%, specifically 20%, 30%, 40%, 50%, 60% or any value between the two ends. The solid content of the acrylic ester polymer can be adjusted according to actual needs and is not limited to the above limited range.

[0032] The present invention performs dual curing by heat curing and light curing. There is no particular limitation on the formula of the acrylate copolymer used in the heat curing system. It can be cured with a heat curing agent to give the adhesive a suitable bonding strength. Therefore, in the dual-curing UV tackifying adhesive of the present invention, various types of heat-curable acrylate copolymers can be used, which has strong universality and is conducive to the development and use of different types of dual-curing UV tackifying adhesives.

[0033] The acrylate copolymer of the present invention can adopt commercially available acrylic glue that meets the above conditions, such as CF-679 produced by Shandong Kafule Polymer Materials Co., Ltd., or it can be homemade by conventional methods.

[0034] The invention provides a self-made acrylic ester copolymer and a preparation method thereof. The acrylic ester copolymer is mainly prepared by copolymerization of acrylic ester monomers; the acrylic ester monomers include soft monomers, hard monomers and functional monomers; based on the total amount of the acrylic ester monomers being 100wt%, the content of the soft monomers is 80wt% to 90wt%, the content of the hard monomers is 5wt% to 10wt%, and the content of the functional monomers is 5wt% to 10wt%.

[0035] For example, in different embodiments, the soft monomer content can be 80wt%, 85wt%, 90wt% or any value between the two end values; the hard monomer content can be 5wt%, 7.5wt%, 10wt% or any value between the two end values; the functional monomer content can be 5wt%, 7.5wt%, 10wt% or any value between the two end values. The present invention helps to ensure the appropriate initial adhesion and good cohesive strength of the adhesive system after thermal curing and before UV irradiation by regulating the ratio of each monomer in the acrylic ester monomer within the above range, so that the adhesive can be pasted and positioned, and can be peeled off from the adhered object without residual adhesive.

[0036] In the present invention, the introduction of functional monomers imparts heat-curable properties to the acrylate copolymer. Regulating the amount of the functional monomers within the above range helps the acrylate copolymer and the thermal curing agent to form a suitable cross-linked network structure after thermal curing, thereby avoiding excessive or insufficient cross-linking, which would prevent the low initial adhesion, reworkability, and subsequent UV light thickening effect from being achieved.

[0037] In a specific embodiment of the present invention, the soft monomer includes at least one of isooctyl acrylate, ethyl acrylate and butyl acrylate.

[0038] In a specific embodiment of the present invention, the hard monomer includes at least one of methyl acrylate and methyl methacrylate.

[0039] In a specific embodiment of the present invention, the functional monomer includes at least one of hydroxyethyl acrylate, hydroxyethyl methacrylate, and hydroxypropyl acrylate.

[0040] In a specific embodiment of the present invention, the acrylic ester copolymer further comprises a thermal initiator and an organic solvent. Relative to 100 parts of the total amount of acrylic ester monomers, the content of the thermal initiator is 0.1 to 1 part, and the content of the organic solvent is 100 to 150 parts. For example, in different embodiments, relative to 100 parts of the total amount of acrylic ester monomers, the content of the thermal initiator can be 0.1 part, 0.3 part, 0.5 part, 0.8 part, 1 part, or any value between any two end values; the content of the organic solvent can be 100 parts, 115 parts, 125 parts, 140 parts, 150 parts, or any value between any two end values.

[0041] In actual operation, in the preparation of the acrylic ester copolymer, the organic solvent may be a conventional solvent, including but not limited to at least one of ethyl acetate, toluene, ethanol, and acetone; the thermal initiator may be a conventional azo initiator, an organic peroxide thermal initiator, etc., and the azo initiator includes but is not limited to at least one of azobisisobutyronitrile and azobisisoheptanenitrile. When the thermal initiator is changed, the reaction temperature for the preparation of the acrylic ester copolymer may be appropriately adjusted to be able to initiate the polymerization of the monomers.

[0042] In a specific embodiment of the present invention, the preparation of the acrylic ester copolymer comprises: weighing raw materials in proportion, and reacting at 65-85° C. for 4-8 hours under a protective atmosphere.

[0043] In the preparation of the acrylic ester copolymer, the protective atmosphere can be nitrogen, but is not limited thereto; the reaction temperature can be 65°C, 70°C, 75°C, 80°C, 85°C or any value between any two ends thereof; the reaction time can be 4h, 5h, 6h, 7h, 8h or any value between any two ends thereof.

[0044] In a specific embodiment of the present invention, the thermal curing agent includes an isocyanate curing agent. Further, the isocyanate curing agent includes at least one of toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI) and diphenylmethane diisocyanate (MDI).

[0045] In a specific embodiment of the present invention, the photoinitiator includes at least one of hydroxycyclohexane phenone and 2-hydroxy-2-methyl-1-phenylpropanone.

[0046] In a specific embodiment of the present invention, a diluent may be added to the dual-curing UV tackifying adhesive. Further, the diluent makes the solid content of the dual-curing UV tackifying adhesive be 20% to 35%, specifically 20%, 25%, 30%, 35% or any value between the two end values.

[0047] In actual operation, whether to use a diluent and the specific amount of the diluent to be used can be selected according to the solid content of the dual-curing UV tackifying adhesive.

[0048] In a specific embodiment of the present invention, the diluent includes at least one of ethyl acetate, toluene and butanone.

[0049] It is understandable that, in order to facilitate production, transportation and sales, the dual-curing UV tackifying adhesive of the present invention only limits the composition of the components but not the existence form of the components, that is, the components can be mixed with each other or stored separately. The mixed or separate storage mode can be selected according to the actual use time.

[0050] The second aspect of the present invention provides an adhesive product, comprising a substrate layer and an adhesive layer disposed on at least one side of the substrate layer; the adhesive layer is mainly made of the dual-curing UV tackifying adhesive described in the first aspect of the present invention.

[0051] The present invention also provides an optional preparation method for the above-mentioned adhesive product, comprising the following steps: mixing the components in proportion, stirring evenly to obtain a mixture; applying the mixture on the surface of the substrate, drying and aging to obtain a dual-curing UV tackifying adhesive product.

[0052] In a specific embodiment of the present invention, drying includes: treating at 100-120° C. for 2-4 min; and aging includes: treating at 55-65° C. for 40-55 h.

[0053] In actual operation, the adhesive layer can be obtained by coating the adhesive on the surface of the substrate and drying and aging. The coating method is not limited, and roller coating, blade coating or dip coating can be used. In actual operation, coating can be carried out using an applicator.

[0054] In a specific embodiment of the present invention, the material of the substrate layer may include at least one of polyethylene terephthalate (PET), polyvinyl chloride (PVC) and polyimide (PI). The thickness of the substrate layer can be freely selected according to actual needs, without special limitation, for example, it can be 10 to 100 μm, specifically 10 μm, 20 μm, 40 μm, 50 μm, 60 μm, 80 μm, 100 μm or any value between the two ends.

[0055] Furthermore, the dual-cured UV tackifying adhesive product also includes a release layer disposed on the other side of the adhesive layer. The release layer may be a PET silicone release film, such as a PET monosilicone release film, and the release force may be 10 to 50 g / 25 mm. The thickness of the release layer may be freely selected according to actual needs without special limitation, for example, it may be set to 5 to 75 μm, specifically 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 75 μm or any value between the two end values.

[0056] In a specific embodiment of the present invention, the thickness of the adhesive layer can be 5 to 25 μm. For example, in different embodiments, the thickness of the adhesive layer can be 5 μm, 10 μm, 20 μm, 25 μm, or a value between any two ends thereof. The thickness of the adhesive layer in the present invention is not easy to be set thicker, because when the adhesive layer is thicker, the UV light will weaken with the thickness of the adhesive layer during UV light curing, and the adhesive layer farther from the UV light is not easy to cure, resulting in a decrease in its bonding strength.

[0057] In a specific embodiment of the present invention, after the adhesive product is attached to the surface of the adhered object and positioned, UV irradiation is performed; wherein the UV irradiation includes: irradiation with UV light of 365nm wavelength; radiation energy of 3,000-4,000mJ / cm 2 .

[0058] The product of the present invention can be designed into other styles such as labels, protective films, and tapes according to actual needs.

[0059] The following specific examples are given to further illustrate the purpose and advantages of the present invention, but these examples should not be considered as limiting the present invention. In the following examples, 1 g represents 1 part by weight.

[0060] Example 1

[0061] 1. The preparation of an acrylate copolymer comprises: placing 85 g of isooctyl acrylate, 7.5 g of methyl acrylate, 7.5 g of hydroxyethyl acrylate and 120 g of ethyl acetate in a reactor, stirring at 65° C. and 140 rpm for 30 min under a nitrogen atmosphere, then adding 0.1 g of azobisisobutyronitrile to react for 90 min, heating to 80° C., adding 0.1 g of azobisisobutyronitrile to react for 4 h, and discharging an acrylate copolymer having a molecular weight of 620,000 g / mol and a solid content of 46%.

[0062] The molecular weight was determined by gel permeation chromatography (GPC), and the specific steps were as follows: the sample was dissolved in tetrahydrofuran (THF) at a concentration of 3-5 mg / mL, and the molecular weight of the sample was tested by GPC, with monodisperse polystyrene (PS) as the standard, THF as the mobile phase, the test flow rate was 1 mL / min, and the injection volume was 20 μL.

[0063] 2. Dual-curing UV tackifying adhesive includes the following components:

[0064] 78 g of the acrylic copolymer prepared in step 1, 20 g of UV polyester resin (manufacturer: Shanghai Santong Material Technology Co., Ltd., model: ST6277, functionality: 3, acid value: 200 mgKOH / g), 1.5 g of hexamethylene diisocyanate (HDI), 0.5 g of hydroxycyclohexane phenone (UV-184) and 107 g of ethyl acetate.

[0065] The preparation method comprises the following steps: uniformly mixing the above-mentioned parts by mass of acrylic ester copolymer, UV polyester resin, HDI and UV-184, adding ethyl acetate to make the solid content of the mixture 28%, and obtaining the adhesive to be coated.

[0066] Example 2

[0067] This example is carried out with reference to Example 1, except that the raw material ratio of the dual-curing UV tackifying adhesive is different, and the preparation method and other components are the same as those of Example 1. The specific differences are as follows:

[0068] The dual-curing UV tackifying adhesive of this embodiment includes the following components: 92 g of acrylate copolymer, 76 g of ST627, 1.7 g of HDI, and 0.3 g of UV-184.

[0069] Example 3

[0070] This example is carried out with reference to Example 1, except that the raw material ratio of the dual-curing UV tackifying adhesive is different, and the preparation method and other components are the same as those of Example 1. The specific differences are as follows:

[0071] The dual-curing UV tackifying adhesive of this embodiment includes the following components: 73 g of acrylate copolymer, 25 g of ST6277, 1 g of HDI, and 1 g of UV-184.

[0072] Example 4 Group

[0073] This embodiment group is carried out with reference to the embodiment 1, and the only difference is that the raw materials of the dual-curing UV tackifying adhesive are different in type and corresponding acid value, and the preparation method and other components are the same as those of the embodiment 1, and the specific differences are as follows:

[0074] Example 4a: The UV polyester resin adopts ST6536 produced by Shanghai Santong Chemical Material Technology Co., Ltd., with an acid value of 25 mgKOH / g and a functionality of 3;

[0075] Example 4b: The UV polyester resin used is ST6207 produced by Shanghai Santong Chemical Material Technology Co., Ltd., with an acid value of 1 mgKOH / g and a functionality of 3.

[0076] Example 5 Group

[0077] This example group was carried out with reference to Example 1, except that the raw materials of the dual-curing UV tackifying adhesive had different types of UV polyester resins, and the corresponding functionalities and acid values ​​were different. The preparation method and other components were the same as those of Example 1, and the specific differences were as follows:

[0078] Example 5a: The UV polyester resin used is L-6125 produced by Guangdong Lanke Road New Materials Co., Ltd., with a functionality of 4 and an acid value of 4 mgKOH / g;

[0079] Example 5b: The UV polyester resin used is L-6120 produced by Guangdong Lanke Road New Materials Co., Ltd., with a functionality of 2 and an acid value of 1 mgKOH / g;

[0080] Example 5c: The UV polyester resin used is L-6129 produced by Guangdong Lanke Road New Materials Co., Ltd., which has a functionality of 6 and an acid value of 1 mgKOH / g.

[0081] Example 6 Group

[0082] This group of examples is carried out with reference to Example 1, the only difference being that the raw materials of the dual-curing UV tackifying adhesive have different components of the acrylate copolymer, and the preparation method and other components are the same as those of Example 1, with the specific differences being as follows:

[0083] Example 6a: 80 g of isooctyl acrylate, 10 g of methyl acrylate, 10 g of hydroxyethyl acrylate, the molecular weight of the acrylate copolymer is 680,000 g / mol;

[0084] Example 6b: 90 g of isooctyl acrylate, 5 g of methyl acrylate, 5 g of hydroxyethyl acrylate, and the molecular weight of the acrylate copolymer is 720,000 g / mol;

[0085] Example 6c: An equal weight of a commercially available acrylic ester copolymer (CF-679 produced by Shandong Kafule Polymer Materials Co., Ltd., with a molecular weight of 1,300,000 g / mol) was used for replacement.

[0086] Comparative Example 1

[0087] This group of comparative examples is carried out with reference to Example 1, except that: the content of UV polyester resin in the adhesive is different, and in order to keep the total amount of the components at 100g, the amount of the acrylic ester copolymer and other substances is adjusted accordingly. The preparation method and other components are the same as those in Example 1, and the specific differences are as follows:

[0088] Comparative Example 1a: 98 g of acrylate copolymer, 2 g of HDI, without UV polyester resin and photoinitiator;

[0089] Comparative Example 1b: 93 g of acrylate copolymer, 5 g of ST6277;

[0090] Comparative Example 1c: 72 g of acrylate copolymer and 26 g of ST6277.

[0091] Comparative Example 2

[0092] This group of comparative examples is carried out with reference to Example 1, except that: the content of the thermal curing agent in the adhesive is different, and in order to keep the total amount of the total components (excluding the solvent) at 100g, the amount of the UV polyester resin is adjusted accordingly. The preparation method and other components are the same as those in Example 1, and the specific differences are as follows:

[0093] Comparative Example 2a: ST6277 21.5 g, without HDI;

[0094] Comparative Example 2b: ST6277 21.2 g, HDI 0.3 g;

[0095] Comparative Example 2c: ST6277 19.7 g, HDI 1.8 g.

[0096] Test Case

[0097] The adhesives prepared in the above embodiments and comparative examples were coated on the surface of a 50 μm thick PET substrate, placed in an oven at 110° C. for 3 min to form a 15 μm thick adhesive layer, and then a PET single silicon release film with a thickness of 15 μm and a release force of 20 g / 25 mm was compounded on the surface of the adhesive layer, aged at 60° C. for 48 h to obtain a test sample, which was stored away from light.

[0098] In order to compare and illustrate the performance differences of the adhesives of different embodiments and comparative examples, the following tests were performed on the test samples prepared in each embodiment and comparative example. The test results are shown in Table 1, and the test methods are referenced as follows.

[0099] Determination of storage modulus: The adhesive prepared in each embodiment and comparative example was coated on a PET single silicon release film with a thickness of 50 μm and a release force of 20 g / 25 mm, and placed in an oven at 110° C. for 3 min to form a 50 μm thick adhesive layer, and then a PET single silicon release film with a thickness of 50 μm and a release force of 20 g / 25 mm was compounded on the surface of the adhesive layer, and aged at 60° C. for 48 h, and the release films on both sides were torn off to obtain an adhesive film, and the adhesive films were multi-layered to 1 mm to obtain a test sample; the test sample was cut into a size of 1 mm in thickness and 8 mm in diameter, and UV light (ultraviolet high-pressure mercury lamp 160 W / cm, 365 nm band, radiation energy 3,500 mJ / cm 2 ) and then use TA rotational rheometer for rheological test. The temperature scanning test uses shear mode, the heating rate is 5℃ / min, the test frequency is 1Hz, the test temperature range is -20~160℃, and the test strain is 0.5%; the film storage modulus value at 25℃ is recorded.

[0100] 180° peel strength test: Cut the sample into 2.5cm wide strips, and the test method is carried out in accordance with the international standard ASTM D3330 "Standard for Peel Strength Test of Pressure-Sensitive Tapes", and the test panel is a steel plate (SUS 304 mirror plate). The 180° peel strength before UV refers to the average adhesion required to tear the strip off the panel after being placed under the test temperature and humidity conditions for 20 minutes after lamination, expressed in gf / 25mm; the 180° peel strength after UV refers to the average adhesion required to tear the strip off the panel after lamination using UV light (ultraviolet high-pressure mercury lamp 160W / cm, 365nm band, radiation energy 3,500mJ / cm 2 ) and then placed under the test temperature and humidity conditions for 20 minutes before testing. The average adhesion required to tear the sample off the panel is expressed in gf / 25mm. The test temperature is 25°C and the humidity is 65%RH.

[0101] Initial adhesion test: The test sample was cut into 2.5 cm wide strips and exposed to UV light (ultraviolet high pressure mercury lamp 160 W / cm, 365 nm band, radiation energy 3,500 mJ / cm 2 ) and then test according to Japanese standard JIS20237 "Rolling ball ramp stop method" and national standard GB / T 4852-2002 "Pressure-sensitive adhesive tape initial adhesion test method (rolling ball method)", and record the maximum steel ball number when stopping. The initial adhesion is generally between 8# ball and 12# ball.

[0102] Heavy-duty test: After the test sample is laminated to a steel plate (SUS 304 mirror plate) at room temperature for 30 minutes, it is quickly torn apart and the surface of the steel plate is observed with an optical microscope at 1,000 times magnification for contamination. If the surface of the steel plate is smooth, clean and pollution-free, it is recorded as OK; if there is white fog attached to the surface of the steel plate or colloid residue, it is recorded as NG.

[0103] Table 1 Test results of different embodiments and comparative examples

[0104]

[0105] From the above test results, it can be seen that the present invention uses a heat-curing system and a light-curing system in combination through the synergy of various components, and the acrylate copolymer is heat-cured with the heat curing agent, so that the adhesive has a relatively low and appropriate bonding force with the adhered object before UV curing, which can be pasted and positioned and conveniently pasted again after peeling; after the UV polyester resin is light-cured, the UV polyester resin is further cross-linked with the acrylate copolymer, so that the peeling force of the adhesive is increased to a level suitable for bonding and fixing. The dual-curing UV tackifying adhesive product of the present invention has a peeling force to a steel plate of 20 to 80 gf / 25 mm before UV irradiation when the thickness of the PET substrate is 50 μm and the thickness of the adhesive layer is 15 μm. This peeling force has initial adhesion and can be peeled off from the surface of the adhered object, thereby ensuring excellent reworkability. After UV irradiation, the peeling force to the steel plate is between 1,000 and 2,500 gf / 25 mm, thereby ensuring bonding stability. The storage modulus is between 68 kPa and 103 kPa. If the modulus is too low, the crosslinking degree of the adhesive is low, thereby resulting in poor bonding performance. If the modulus is too high and the crosslinking density is too large, the adhesive is too hard, the wetting ability is reduced, and thus the colloid bonding performance is reduced.

[0106] It can be seen from the test results of Example 4 that the present invention further limits the acid value of the UV polyester resin, which can further ensure the initial adhesion and tackifying effect of the adhesive.

[0107] It can be seen from the test results of Example 5 that the present invention further limits the functionality of the UV polyester resin, which can further ensure the initial adhesion and tackification effects of the adhesive; if the functionality of the UV polyester resin is low, then after UV irradiation, its crosslinking degree is insufficient, the storage modulus is low, the adhesion to the adhered object decreases, and the initial adhesion is low; if the functionality of the UV polyester resin is large, then after UV irradiation, its crosslinking density is too large, the colloid is too hard, resulting in poor wettability with the adhered object, low initial adhesion, and large storage modulus, and the tackification effect is not obvious.

[0108] The test results of Example 6 show that in the dual-curing UV tackifying adhesive of the present invention, an acrylate copolymer with a wider molecular weight range can be used, and commercially available acrylic glue is also applicable, which has a certain universality and can reduce the steps of the synthesis process.

[0109] The test results of comparative example 1 show that if the adhesive of the present invention does not contain UV polyester resin, the UV tackification effect cannot be achieved. If the amount of UV polyester resin is too low, the tackification effect is poor and the initial adhesion is low; if the amount of UV polyester resin is too high, debonding will occur after UV due to excessive crosslinking.

[0110] It can be seen from the test results of comparative example 2 that if the adhesive of the present invention does not contain a thermal curing agent, the colloid will be too soft to achieve effective bonding and degumming will occur; if the amount of the thermal curing agent is too low, the pre-UV peeling force will be high, and the modulus after UV will be low, resulting in degumming; if the amount of the thermal curing agent is too high, the modulus of the entire colloid will increase, the hardness will increase, the wetting performance will be poor, and the UV viscosity-increasing effect will be poor.

[0111] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. Dual-curing UV tackifying adhesive, characterized in that: It includes the following components by weight:

2. The dual-curing UV tackifying adhesive according to claim 1, characterized in that: The acid value of the UV polyester resin is ≤220 mgKOH / g; And / or, the functionality of the UV polyester resin is 3-4.

3. The dual-curing UV tackifying adhesive according to claim 1, characterized in that: The storage modulus of the UV tackifying adhesive at 25° C. after UV curing is 68 to 103 kPa.

4. The dual-curing UV tackifying adhesive according to claim 1, characterized in that: The molecular weight of the acrylic ester copolymer is 100,000 to 1,300,000 g / mol.

5. The dual-curing UV tackifying adhesive according to claim 1 or 4, characterized in that: The acrylic ester copolymer is mainly prepared by copolymerization of acrylic ester monomers; the acrylic ester monomers include soft monomers, hard monomers and functional monomers; based on the total amount of the acrylic ester monomers as 100wt%, the content of the soft monomers is 80wt% to 90wt%, the content of the hard monomers is 5wt% to 10wt%, and the content of the functional monomers is 5wt% to 10wt%.

6. The dual-curing UV tackifying adhesive according to claim 1, characterized in that: The thermal curing agent includes an isocyanate curing agent.

7. The dual-curing UV tackifying adhesive according to claim 6, characterized in that: The isocyanate curing agent includes at least one of toluene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate and diphenylmethane diisocyanate.

8. The dual-curing UV tackifying adhesive according to claim 1, characterized in that: The photoinitiator includes at least one of hydroxycyclohexane phenone and 2-hydroxy-2-methyl-1-phenylpropanone.

9. An adhesive product, characterized in that: The invention comprises a substrate layer and an adhesive layer arranged on at least one side of the substrate layer; the adhesive layer is mainly made of the dual-curing UV tackifying adhesive according to any one of claims 1 to 8.

10. The product according to claim 9, characterized in that The thickness of the adhesive layer is 5 to 25 μm.

Citation Information

Cited By

  • Tackifying type functional film and preparation method thereof

    CN121759105A

  • Functional film with responsively increased viscosity and preparation method thereof

    CN122104084A